2008
DOI: 10.1016/j.juro.2008.01.106
|View full text |Cite
|
Sign up to set email alerts
|

Predicting an Optimal Outcome After Radical Prostatectomy: The Trifecta Nomogram

Abstract: Purpose-The optimal outcome after radical prostatectomy (RP) for clinically localized prostate cancer is freedom from biochemical recurrence (BCR) along with recovery of continence and erectile function, a so-called trifecta. We evaluated our series of open radical prostatectomy patients to determine the likelihood of this outcome and to develop a nomogram predicting the trifecta. Material and Methods-We reviewed records of patients undergoing open RP for clinical stageT1c-T3a prostate cancer at our center dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
129
0
7

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 179 publications
(142 citation statements)
references
References 8 publications
4
129
0
7
Order By: Relevance
“…Postoperative urinary continence outcomes for RARP, LRP, and RRP are tabulated in Table 7, 16,17,[23][24][25]27,[32][33][34][35][59][60][61] Table 9. 35,48,50,51,53,58,63,64 Direct comparisons for urinary continence rates between different prostatectomy series are difficult because of variations in definitions, data collection methods, and length of follow-up.…”
Section: Urinary Continence Outcomesmentioning
confidence: 99%
“…Postoperative urinary continence outcomes for RARP, LRP, and RRP are tabulated in Table 7, 16,17,[23][24][25]27,[32][33][34][35][59][60][61] Table 9. 35,48,50,51,53,58,63,64 Direct comparisons for urinary continence rates between different prostatectomy series are difficult because of variations in definitions, data collection methods, and length of follow-up.…”
Section: Urinary Continence Outcomesmentioning
confidence: 99%
“…Several trials have indicated that the best postoperative potency rates are obtained in the younger patient population. [11][12][13][14] Younger patients are more likely to have better preoperative erectile function and to be more interested in sexual recovery after surgery. [11][12][13][14] Patients between ages 40 years and 49 years reported rates of erectile function recovery as high as 92%.…”
Section: Patient and Partner Agementioning
confidence: 99%
“…Several studies have demonstrated that the surgical approach is key for maintaining erectile function after RP. [11][12][13][14] Indeed, the volume of neural tissue preserved is associated linearly with the quality of erection after surgery. Patients with both NVBs preserved are more likely to recover erectile function after surgery (Table 1).…”
Section: Cormorbidity Profilementioning
confidence: 99%
See 1 more Smart Citation
“…Of note, individually,P SA free survival, continence and potency rates were 85%, 66% and 33%, respectively.Bianco et al reported aT rifecta rate of 60% at 2y ears after RRP (45). Morer ecently, Eastham et al described their Trifecta rate at 62% at 2 years (46). Only one report of outcomes in RARP patients is available.…”
Section: Trifectaoutcomesmentioning
confidence: 99%